EFEKTIVITAS METODE TANYA JAWAB DALAM MENINGKATKAN KEAKTIFAN BELAJAR SISWA KELAS 4 SD/MI PADA PEMBELAJARAN IPS - Yona Anisa Fitri; Ulva Nabila; Tyara Wahyuni; Wafitri Oktaviani; Susi Ratna Sari (STKIP Subang, 2026)
This study aims to analyze the effectiveness of the question and answer method in enhancing the learning activeness of fourth-grade elementary school students in Social Studies (IPS) subjects. The research employs a qualitative method with a literature review approach, analyzing various relevant sources including national and international journals, books, and previous research findings related to the topic. Data collection was conducted through reading, reviewing, and synthesizing information from selected literature, followed by comparative analysis, summarization, and conclusion drawing. The results indicate that the question and answer method is effective in improving various aspects of student learning engagement, including learning motivation, questioning skills, response time, discussion participation, and overall learning outcomes. In fourth-grade students at SDN 3 Ogotua, learning mastery increased from 50% in the pre-action stage to 87.5% in cycle I and 100% in cycle II. The application of the question ball technique at SDN 2 Bantar increased student motivation scores from 53 (moderate category) to 82 (high category), a gain of 29 points. Statistical hypothesis testing at SDN 98 Palembang showed t-count = 3.815 > t-table = 2.010, confirming that the question and answer method has a significant effect on student learning outcomes. The success of this method is highly dependent on the teacher's questioning skills and the ability to create a supportive classroom atmosphere. The question and answer method is also aligned with the concrete operational stage of cognitive development in children aged 9-10 years according to Piaget's theory. This study recommends that teachers plan key questions hierarchically, provide adequate wait time, distribute questions evenly, and integrate the method with concrete learning media for optimal results.